A method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy
By performing heat treatment and sandblasting pretreatment on the surface of eutectic high-entropy alloy, combined with DC glow ion nitriding technology, the problem of difficult to prepare high hardness and high wear-resistant nitriding layers on the surface of eutectic high-entropy alloy is solved, and a significant improvement has been achieved Effects of surface hardness and wear resistance.
Patent Information
- Application Number
- CN202310496633.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-05-05
AI Technical Summary
The prior art is difficult to effectively prepare high hardness and high wear-resistant nitriding layers on the surface of eutectic high entropy alloys, and single-phase high entropy alloys are difficult to balance between strength and ductility.
The eutectic high-entropy alloy is surface nitrided by a DC glow ion nitriding furnace. The pretreatment includes heat treatment and sandblasting treatment to stabilize the alloy structure and prefabricate the stress, thereby improving the nitriding rate and effect in the nitriding treatment.
A high-hardness and high wear resistance nitriding layer was successfully prepared on the surface of eutectic high-entropy alloy, which significantly improved the surface hardness and wear resistance of the alloy and broadened its application prospects in engineering applications.
Smart Images

Figure CN116752082B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy surface nitriding treatment, and specifically relates to a method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy. Background Art
[0002] Ion nitriding is a chemical heat treatment method that forms a nitride layer on the surface of the substrate to improve the surface performance of parts. It can give the surface of parts high hardness, high wear resistance, high corrosion resistance, oxidation resistance, fatigue resistance and other special properties. It is an important means of strengthening the surface of parts. This method is green, environmentally friendly, energy-saving, and is increasingly widely used.
[0003] High entropy alloy, also known as multi-principal alloy, as a new type of alloy material, has attracted many researchers to conduct extensive research on it after its birth; it was found that single-phase high entropy alloys were difficult to balance the strength and ductility of the alloy, so the researchers introduced the concept of eutectic alloys into the preparation of high entropy alloys and newly developed eutectic high entropy alloys; eutectic high entropy alloys are the high entropy alloy materials closest to engineering applications due to their excellent casting properties.
[0004] At present, there are related studies on the preparation of nitriding layers in single-phase high-entropy alloys. However, single-phase high-entropy alloys cannot meet the balance of strength and plasticity due to their organization and structure. Eutectic high-entropy alloys can well balance plasticity and strength because of their layered eutectic structure formed by a softer face-centered cubic phase and a harder body-centered cubic phase. Researchers have found that eutectic high-entropy alloys have better casting fluidity, which can save costs. Surface nitriding of eutectic high-entropy alloys to improve their surface properties can increase the prospects of high-entropy alloys in engineering applications.
[0005] In order to expand the engineering application of high entropy alloys, the inventors used a DC glow ion nitriding furnace to nitridate the surface of the eutectic high entropy alloy. 19 Fe 20 Co 20 Ni 41 Considering its cost and performance, eutectic high entropy alloy is an ideal matrix material for eutectic high entropy alloy with surface nitridation. Surface nitridation can improve its surface hardness and wear resistance, thus broadening the application prospects of this material. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0010] A eutectic high entropy alloy matrix is prepared, and the matrix is pretreated and then ion nitrided, and a high-hardness and high-wear-resistant nitrided layer is prepared on the surface of the matrix after the treatment is completed;
[0011] Wherein, the pretreatment includes heat treatment and sandblasting.
[0012] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the method for preparing the eutectic high-entropy alloy substrate comprises:
[0013] Al, Fe, Co, and Ni are used as the main elements. After mixing, they are placed in a vacuum induction melting furnace. The raw materials are evacuated and heated to melt evenly. Then they are quickly poured into a mold and cooled in the furnace to form a square ingot.
[0014] The atomic percentages of the elements are: Al: 18-20 at.%, Co: 20-22 at.%, Fe: 20-22 at.%, Ni: 40-45 at.%.
[0015] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the heat treatment comprises a treatment temperature of 400 to 600°C and a treatment time of 5 to 30 minutes.
[0016] As a preferred scheme of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy described in the present invention, the sandblasting conditions of the sandblasting pretreatment include an air intake pressure of 0.4 to 0.6 MPa, a sandblasting pressure of 0.4 to 0.6 MPa, a spraying angle of 45 to 90°, and a sandblasting time of 5 to 10 min.
[0017] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the ion nitriding treatment comprises:
[0018] The pretreated eutectic high entropy alloy is placed on the cathode plate of the nitriding furnace, the nitriding furnace is sealed, and after power is turned on, the vacuum pump is turned on to evacuate the furnace;
[0019] When the gas pressure in the furnace is stable, slowly adjust the working voltage and current, and introduce hydrogen to produce a glow in the furnace;
[0020] The glow discharge phenomenon is used to increase the temperature in the furnace, and the gas pressure and hydrogen flow rate in the furnace are constantly adjusted to clean the alloy surface by sputtering;
[0021] After sputtering, nitrogen is introduced to maintain the gas ratio of hydrogen to nitrogen at 1-2:3-4. After the temperature in the furnace stabilizes, insulation treatment is performed to finally obtain a nitriding layer.
[0022] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy described in the present invention, the continuous adjustment of the gas pressure and hydrogen flow rate in the furnace is to adjust the gas pressure to 280-320 Pa and the hydrogen flow rate to 480-520 mL / min.
[0023] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the sputtering cleaning is performed for a sputtering time of 25 to 35 minutes.
[0024] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy described in the present invention, the gas pressure in the furnace during the insulation treatment is 380-420 Pa, the insulation temperature is 500-550° C., and the insulation time is 2-6 hours.
[0025] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the thickness of the nitriding layer is 1 to 10 μm.
[0026] As a preferred embodiment of the method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to the present invention, the surface hardness of the alloy is 584-803 HV, and the wear rate is less than 10 -5 N mm / mm 3 .
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention performs nitriding treatment on a eutectic high entropy alloy close to engineering applications, forming a nitriding layer with high hardness and high wear resistance on its surface, which greatly improves the surface hardness and wear resistance of the alloy in the cast state;
[0029] (2) The present invention introduces heat treatment and sandblasting to pretreat the surface of the eutectic high entropy alloy substrate during the process of preparing the nitriding layer. The structure is stabilized by heat treatment, and the stress is preformed by sandblasting. The pretreated substrate can greatly increase the nitriding rate and shorten the nitriding time during nitriding treatment, while also improving the nitriding effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0031] Figure 1 It's Al 19 Fe 20 Co 20 Ni 41 Original surface microstructure of eutectic high entropy alloy.
[0032] Figure 2 It's Al 19 Fe 20 Co 20 Ni 41 XRD pattern of eutectic high entropy alloy.
[0033] Figure 3 This is the microstructure of the cross section of the nitrided layer of the nitrided sample in Example 2 of the present invention.
[0034] Figure 4 This is a cross-sectional line scanning EDS energy spectrum of the nitriding treated sample in Example 2 of the present invention.
[0035] Figure 5 This is a cross-sectional surface scanning EDS energy spectrum of the nitriding treated sample in Example 2 of the present invention.
[0036] Figure 6 This is the XRD spectrum of the nitriding treated sample in Example 2 of the present invention.
[0037] Figure 7 It is a metallographic image of the cross-section microstructure of the nitrided layer of the nitrided sample according to Example 3 of the present invention.
[0038] Figure 8 It is a metallographic image of the cross-section microstructure of the nitrided layer of the nitrided sample according to Example 4 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0042] The ion nitriding furnace used in the present invention is a direct current glow ion nitriding furnace, and the hydrogen and nitrogen introduced into the nitriding furnace are ordinary nitrogen and hydrogen with a purity of 99.9%.
[0043] Example 1
[0044] This embodiment provides a method for preparing a eutectic high entropy alloy, which is as follows:
[0045] With Al, Fe, Co, Ni and other elements as main elements, the atomic percentages of the elements are: Al: 18-20at.%, Co: 20-22at.%, Fe: 20-22at.%, Ni: 40-45at.%;
[0046] After mixing, put it into a vacuum induction melting furnace. The temperature of the induction melting furnace is 1500℃ and the vacuum degree in the furnace is less than 1×10- 5 Pa, induction current 200A ~ 600A, vacuum and heat to melt the raw materials evenly, ensure that all metals are in liquid state and keep for 10 to 15 minutes, then quickly pour into the mold, cool with the furnace into a square ingot, and obtain Al 19 Fe 20 Co 20 Ni 41 Eutectic high entropy alloy.
[0047] The eutectic high entropy alloy prepared in this embodiment can have good tensile properties without conventional heat treatment and deformation treatment after casting.
[0048] Figure 1 The Al prepared in this embodiment 19 Fe 20 Co 20 Ni 41 The original surface structure of the eutectic high entropy alloy. Figure 2 For Al 19 Fe 20 Co 20 Ni 41 XRD spectrum of eutectic high entropy alloy, the hardness of the alloy matrix was determined to be 311HV.
[0049] The following embodiments are all based on the eutectic high entropy alloy prepared in this embodiment.
[0050] Example 2
[0051] This embodiment provides a method for preparing Al 19 Fe 20 Co 20 Ni 41 The preparation method of the ion nitriding layer on the surface of the eutectic high entropy alloy comprises the following specific steps:
[0052] Heat treatment: Al 19 Fe 20 Co 20 Ni 41 The eutectic high entropy synthesis was kept at 600 °C for 30 min;
[0053] Sandblasting pretreatment: The heat-treated square ingot was cut into small samples of 10×10×3 mm by wire cutting, and the surface was ground and polished, and sandblasting pretreatment was performed until the sample surface was uniform. The sandblasting conditions were as follows: air intake pressure 0.5 MPa, sandblasting pressure 0.5 MPa, spray angle 90°, and sandblasting time 5 min.
[0054] Ion nitriding treatment: Slowly open the gas valve to make the pressure in the nitriding furnace consistent with the pressure in the air, then lift the nitriding furnace wall, use sandpaper, alcohol, etc. to clean the cathode disk in the nitriding furnace, and then place the sandblasted sample on the cathode disk in the nitriding furnace; lower the furnace wall, and then use vacuum mud to seal it;
[0055] Open the vacuum pump valve and cooling water valve to evacuate the furnace. When the pressure in the furnace is stable, adjust the voltage and current and introduce hydrogen to generate glow discharge in the furnace.
[0056] The temperature in the nitriding furnace was raised by using the glow discharge phenomenon, and then the hydrogen gas flow rate and the gas pressure in the furnace were continuously adjusted. The hydrogen gas flow rate was adjusted to 300 mL / min. When the pressure in the furnace was adjusted to 300 Pa, sputtering was performed for 30 minutes.
[0057] After sputtering, nitrogen was introduced, and the ratio of the mixed gas in the furnace was kept at H2:N2=1:3, and then the temperature was kept at 550℃ and 400Pa for 6h;
[0058] After the insulation is completed, turn off the voltage and current, turn off the gas cylinder and the vacuum pump. After the nitriding furnace has cooled down, the nitriding furnace can be opened and the sample can be taken out, and a nitriding layer will be formed on the surface of the substrate.
[0059] Figure 3 The microstructure of the cross section of the infiltration layer of the sample obtained in this embodiment is as follows: Figure 4 For its cross-sectional line scanning EDS spectrum, Figure 5 Scan the EDS spectrum of its cross section. Figure 6 is the XRD pattern of the sample.
[0060] Figure 5The thickness of the nitrided layer of the sample compound obtained in this embodiment is about 10 μm, and the surface hardness is significantly improved from 311 HV to 803 HV compared with the substrate hardness. Figure 6 As shown in the figure, the surface performance is significantly improved due to the formation of nitrides. The improvement of surface hardness can improve the wear resistance of the material. The wear rate of the sample prepared in this embodiment is less than 10 -5 N mm / mm 3 .
[0061] Example 3
[0062] The difference between this embodiment and embodiment 2 is that the insulation time of introducing nitrogen after sputtering is 2 hours, and the rest of the preparation process is the same as that of embodiment 2.
[0063] The microstructure of the cross section of the infiltration layer is as follows Figure 7 As shown, its surface hardness is significantly improved from 311HV to 584HV compared with the matrix hardness.
[0064] Example 4
[0065] The difference between this embodiment and embodiment 2 is that the insulation time of introducing nitrogen after sputtering is 4 hours, and the rest of the preparation process is the same as that of embodiment 2.
[0066] The microstructure of the cross section of the infiltration layer is as follows Figure 8 As shown, its surface hardness is significantly improved from 311HV to 716HV compared with the matrix hardness.
[0067] Example 5
[0068] The difference between this embodiment and embodiment 2 is that the sandblasting angle is adjusted to 45°, and the rest of the preparation process is the same as that of embodiment 2. The surface hardness of the sample prepared in this embodiment is measured to be 778 HV.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 3 is that the sandblasting angle is adjusted to 45°, and the rest of the preparation process is the same as that of embodiment 3. The surface hardness of the sample prepared in this embodiment is measured to be 545 HV.
[0071] Example 7
[0072] The difference between this embodiment and embodiment 4 is that the sandblasting angle is adjusted to 45°, and the rest of the preparation process is the same as that of embodiment 4. The surface hardness of the sample prepared in this embodiment is measured to be 716 HV.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 2 is that no sandblasting pretreatment is performed, and the rest of the preparation process is the same as that of Example 2. The surface hardness of the sample prepared in this example is measured to be 568 HV.
[0075] Comparative Example 2
[0076] The difference between this comparative example and Example 3 is that no sandblasting pretreatment is performed, and the rest of the preparation process is the same as that of Example 2. The surface hardness of the sample prepared in this example is measured to be 533 HV.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 4 is that no sandblasting pretreatment is performed, and the rest of the preparation process is the same as that of Example 2. The surface hardness of the sample prepared in this example is measured to be 544 HV.
[0079] The surface hardness results of the samples obtained in the above Examples 2 to 7 and Comparative Examples 1 to 3 are shown in Table 1.
[0080] Table 1 Surface hardness of samples after different sandblasting and nitriding time at 550℃ nitriding temperature
[0081] 6h 2h 4h 45 degree sandblasting 778HV 545HV 603HV 90 degree sandblasting 803HV 584HV 716HV No sandblasting 568HV 533HV 544HV
[0082] It can be seen from Table 1 that the present invention has a significant effect on the hardness of the nitrided coating by adjusting the sandblasting conditions and the nitriding time. In the scheme of the present invention, the nitriding efficiency can be significantly improved by introducing the sandblasting pretreatment, and a better effect can be achieved in a shorter treatment time; and the nitriding effect can be further improved by adjusting the sandblasting angle.
[0083] Example 8
[0084] This example is used to explore the effect of the coating obtained when the nitriding temperature is 400°C.
[0085] The difference between this embodiment and embodiment 2 is that the nitriding temperature is adjusted to 400°C, and on this basis, the sandblasting conditions and the nitriding time are adjusted. The rest of the preparation process is the same as that of embodiment 2. The specific parameters and results are shown in Table 2.
[0086] Table 2 Surface hardness of samples after different sandblasting and nitriding time at 400℃ nitriding temperature
[0087] 6h 2h 4h 45 degree sandblasting 437HV 411HV 426HV 90 degree sandblasting 465HV 435HV 452HV No sandblasting 410HV 384HV 395HV
[0088] It can be seen from Table 2 that under the same treatment process conditions, when the nitriding temperature is adjusted to 400°C, the performance of the nitrided coating is greatly reduced compared with the nitriding temperature of 550°C, and the hardness is not significantly improved compared with the substrate that has not been nitrided, indicating that at a nitriding temperature of 400°C, the performance of the nitrided coating does not have a significant advantage.
[0089] Example 9
[0090] This example is used to explore the effect of the coating obtained when the nitriding temperature is 500°C.
[0091] The difference between this embodiment and embodiment 2 is that the nitriding temperature is adjusted to 500°C, and on this basis, the sandblasting conditions and the nitriding time are adjusted. The rest of the preparation process is the same as that of embodiment 2. The specific parameters and results are shown in Table 3.
[0092] Table 3 Surface hardness of samples after different sandblasting and nitriding time at 500℃ nitriding temperature
[0093] 6h 2h 4h 45 degree sandblasting 505HV 468HV 486HV 90 degree sandblasting 545HV 501HV 523HV No sandblasting 421HV 411HV 418HV
[0094] It can be seen from Table 3 that under the same treatment process conditions, when the nitriding temperature is adjusted to 500°C, the performance of the nitrided coating is improved compared with the nitriding temperature of 400°C, but there is still a certain gap compared with the nitriding temperature of 550°C. At the same time, combined with Table 1, it can be seen that when the temperature is increased from 500°C to 550°C, the hardness of the substrate is significantly improved.
[0095] In summary, it can be seen that in the process of preparing the nitriding layer, the present invention introduces sandblasting to pretreat the surface of the eutectic high entropy alloy substrate. The substrate after sandblasting pretreatment can greatly increase the nitriding rate and shorten the nitriding time during nitriding treatment, while also improving the nitriding effect. The present invention further explores the influence of nitriding conditions on coating performance, thereby obtaining the optimal nitriding temperature and time, thereby broadening the application prospects of this material.
[0096] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy, characterized in that: include, Al, Fe, Co, and Ni elements are used as main elements, mixed and put into a vacuum induction melting furnace, vacuumed and heated to melt the raw materials evenly, quickly poured into a mold, cooled into a square cast with the furnace, and a eutectic high entropy alloy matrix is prepared, wherein the atomic percentages of the elements are: Al: 18~20at.%, Co: 20~22at.%, Fe: 20~22at.%, Ni: 40~45at.%; After the substrate is subjected to heat treatment and sandblasting treatment, an ion nitriding treatment is performed, and a high-hardness and high-wear-resistant nitriding layer is obtained on the substrate surface after the treatment is completed; Wherein, the treatment temperature of the heat treatment is 400-600°C, and the treatment time is 5-30min; The blasting conditions of the blasting treatment are as follows: an air intake pressure of 0.4-0.6 MPa, a blasting pressure of 0.4-0.6 MPa, a jet angle of 45-90°, and a blasting time of 5-10 min.
2. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to claim 1, characterized in that: The ion nitriding treatment comprises: The pretreated eutectic high entropy alloy is placed on the cathode plate of the nitriding furnace, the nitriding furnace is sealed, and after power is turned on, the vacuum pump is turned on to evacuate the furnace; When the gas pressure in the furnace is stable, slowly adjust the working voltage and current, and introduce hydrogen to produce a glow in the furnace; The glow discharge phenomenon is used to increase the temperature in the furnace, and the gas pressure and hydrogen flow rate in the furnace are constantly adjusted to clean the alloy surface by sputtering; After sputtering, nitrogen is introduced to maintain the gas ratio of hydrogen to nitrogen at 1~2:3~4. After the temperature in the furnace stabilizes, insulation treatment is performed to finally obtain a nitriding layer.
3. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to claim 2, characterized in that: The continuous adjustment of the gas pressure and hydrogen flow rate in the furnace is to adjust the gas pressure to 280-320 Pa and the hydrogen flow rate to 480-520 mL / min.
4. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to claim 2, characterized in that: The sputtering cleaning, wherein the sputtering time is 25 to 35 minutes.
5. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to claim 2, characterized in that: During the heat preservation treatment, the gas pressure in the furnace is 380-420 Pa, the heat preservation temperature is 500-550° C., and the heat preservation time is 2-6 hours.
6. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to any one of claims 1 to 5, characterized in that: The thickness of the nitriding layer is 1-10 μm.
7. The method for preparing a high-hardness and high-wear-resistant nitriding layer on the surface of a eutectic high-entropy alloy according to any one of claims 1 to 5, characterized in that: The alloy surface hardness is 584~803 HV, and the wear rate is less than 10 -5 N mm / mm 3 .
Citation Information
Patent Citations
Method for preparing surface plasma nitrided layer of high-entropy alloy
CN106637062A
High-strength and high-plasticity eutectic high-entropy alloy and preparation method thereof
CN108642363A